Structured Mentoring for Dissertation Proposal Development: A Community Service Model for Strengthening Research Capacity among Educators and Government Professionals - Dwi Sulisworo; Ika Maryani; Asyraf Suryadin (Journal of Social and Community Development, 2026)
Research competence is a critical requirement for doctoral students and professionals pursuing advanced academic qualifications. However, many doctoral candidates from diverse professional backgrounds experience challenges in developing structured dissertation proposals due to limited research experience, methodological understanding, and academic writing skills. This community service program aimed to strengthen participants’ research capacity through a structured mentoring intervention conducted over two days on February 21–22, 2026. The participants included teachers, lecturers, and government professionals with diverse academic and professional backgrounds. The program utilized structured mentoring, guided practice, collaborative discussion, and iterative feedback. This study employed a qualitative descriptive approach using observation, proposal document analysis, and participant reflections. The conceptual framework was based on adult learning theory, experiential learning, and research capacity development models. The findings demonstrate significant improvements in research problem formulation, conceptual framework development, proposal structure, and research confidence. Participant diversity was identified as both a challenge and an opportunity for collaborative learning. Structured mentoring proved effective in strengthening research competence across heterogeneous participant groups. This community service model provides a scalable and effective framework for research capacity development and can be implemented by higher education institutions to support doctoral students and professional researchers.